Serum α-linolenic and other ω-3 fatty acids, and risk of disabling dementia: Community-based nested case–control study. Issue 3 (June 2017) - Yamagishi, Kazumasa; Ikeda, Ai; Chei, Choy-Lye; Noda, Hiroyuki; Umesawa, Mitsumasa; Cui, Renzhe; Muraki, Isao; Ohira, Tetsuya; Imano, Hironori; Sankai, Tomoko; Okada, Takeo; Tanigawa, Takeshi; et al.
Summary: Background & aims: It has been hypothesized that ω-3 polyunsaturated fatty acids have anti-atherosclerotic and neuronal protective functions and may benefit prevention of dementia, but the epidemiological evidence, especially for α-linolenic acid, is quite limited. The aim of this study was to examine whether serum ω-3 polyunsaturated fatty acids are associated with risk of dementia. Methods: We performed an intracohort case–control study nested in a community-based cohort, the Circulatory Risk in Communities Study, involving 7586 Japanese individuals aged 40–74 years at the baseline period of 1984–1994. Omega-3 polyunsaturated fatty acid constituents (α-linolenic, eicosapentaenoic, and docosahexaenoic acids) in serum total lipid were measured in 315 cases of incident disabling dementia in the above-mentioned cohort between 1999 and 2004, and in 630 controls whose age, sex, area, and baseline year were matched with the cases. Results: As we had postulated, serum α-linolenic acid was inversely associated with risk of disabling dementia: the multivariate odds ratios (95% confidence intervals) were 0.57 (0.39–0.85), 0.51 (0.34–0.76), and 0.61 (0.41–0.90) for persons with the second, third, and highest quartiles of serum α-linolenic acid, respectively, as compared with the lowest quartile ( P for trend = 0.01). Associations of other ω-3 fatty acids with disabling dementia were not statistically significant. Conclusions: Serum α-linolenic acid was inversely associated with risk of disabling dementia. Although the causality needs to be confirmed by randomized control trials, we identified serum α-linolenic acid as a biomarker that predicts future dementia.